PENGARUH DENTAL HEALTH EDUCATION BERBASIS VIDEO ANIMASI DAN E-SAKU GIGI PADA ANAK USIA 7-12 TAHUN - Arini Indriyasari; Pritha Kunti Nali Broto (Jurnal Kesehatan dan Pembangunan, 2026)
Dental caries and oral hygiene are common problems in children. This condition is caused by low levels of knowledge, attitudes, and behavior regarding proper toothbrushing. This study aims to determine the effect of Dental Health Education (DHE) based on animated videos and dental e-pockets on the OHI-S and DMFT status of children aged 7 to 12 years at the Kediri City Community Health Center. The study used a quantitative true experimental design with a sample of 200 respondents obtained through simple random sampling. Data were collected using questionnaires, OHI-S examinations, DMFT examinations, observation, and documentation. The results showed that the average OHI-S and DMFT decreased. The paired t-test showed significant differences in OHI-S (p = 0.000162) and DMFT (p = 0.0003). Dental Health Education interventions based on animated videos and dental e-pockets were effective in improving children's oral and dental health.